2019
DOI: 10.1002/ceat.201800248
|View full text |Cite
|
Sign up to set email alerts
|

Co‐processing of Waste Cooking Oil and Light Cycle Oil with NiW/(Pseudoboehmite + SBA‐15) Catalyst

Abstract: Light cycle oil (LCO) and waste sunflower cooking oil (WSO) were co‐processed with the aim of obtaining more environmentally friendly fuels. Partial hydrogenation of naphthalene was also investigated as a model reaction. Commercial NiW/SiO2‐Al2O3, as a reference catalyst, and NiW/(pseudoboehmite + SBA‐15), as a new research catalyst, were tested. Liquid products were analyzed by simulated distillation, elemental analysis, and FTIR spectroscopy. Elemental analysis indicated higher efficiency of the research cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Di-t-butyl polysulfide (LU) was obtained from Lubrizol (Wicklie, OH, USA). The NiW/SiO 2 -Al 2 O 3 commercial catalyst (CC) containing 6.4 wt % W and 17.5 wt % Ni was used [30]. The second used catalyst was a laboratory-prepared catalyst on a phonolite support (PH) with 5 wt % Ni and 10 wt % W [26].…”
Section: Methodsmentioning
confidence: 99%
“…Di-t-butyl polysulfide (LU) was obtained from Lubrizol (Wicklie, OH, USA). The NiW/SiO 2 -Al 2 O 3 commercial catalyst (CC) containing 6.4 wt % W and 17.5 wt % Ni was used [30]. The second used catalyst was a laboratory-prepared catalyst on a phonolite support (PH) with 5 wt % Ni and 10 wt % W [26].…”
Section: Methodsmentioning
confidence: 99%
“…It is widely used in the industry for hydrocracking petroleumheavy fractions to produce suitable light products. The same catalyst has been used by the authors and reported in previous references [36,37]. As the catalyst was commercially sourced, detailed information about the fresh or used catalyst samples is not included in the manuscript.…”
Section: Feedstocks and Catalystmentioning
confidence: 99%
“…The hydrotreating with hydrogen of most vegetable oils in the presence of metal oxide catalysts, leads to the production of a liquid blend of C15-C18 hydrocarbons, exhibiting a boiling point within the range of diesel, so that it is commonly called "green diesel", "renewable diesel", or "bio-hydrogenated diesel", and therefore with the same chemical behavior that petroleum-derived diesel. This technology has been extended to the application of hydrocracking treatments to mixtures of vegetable oils with fractions of heavy petroleum crude, of equivalent molecular weights in conventional oil refineries [355][356][357][358][359][360][361][362][363][364][365][366][367][368][369][370][371][372][373][374]. Therefore, this procedure makes possible to transform triglycerides into high quality diesel fuel, with the facilities already available in conventional oil refineries, using specific catalysts.…”
Section: Fossil Diesel-like Biofuels: Green Diesel From Hydrotreated mentioning
confidence: 99%